2020
DOI: 10.1002/pd.5765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and evidence of vertical transmission of infections in pregnancy including SARS‐CoV‐2s

Abstract: There remain unanswered questions concerning mother-to-child-transmission of SARS-CoV-2. Despite reports of neonatal COVID-19, SARS-CoV-2 has not been consistently isolated in perinatal samples, thus definitive proof of transplacental infection is still lacking. To address these questions, we assessed investigative tools used to confirm maternal-fetal infection and known protective mechanisms of the placental barrier that prevent transplacental pathogen migration. Forty studies of COVID-19 pregnancies reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 148 publications
(257 reference statements)
3
81
1
15
Order By: Relevance
“…Of these, Placental Endonuclease, Poly(U) Specific (ENDOU, placental protein 11 or PP11), which has high homology with the coronavirus endoribonuclease Nsp15 [ 13 ] ( Fig. 1 C), and Human Angiotensin-Converting Enzyme 2 (ACE2), the cellular entry receptor for SARS-CoV-2 [ 14 , 15 ] were specifically selected for validation by RT-PCR and IHC. Additionally, placental RNAseq transcript abundance mapped to ENDOU’s PPI network suggests putative interactions of ENDOU ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, Placental Endonuclease, Poly(U) Specific (ENDOU, placental protein 11 or PP11), which has high homology with the coronavirus endoribonuclease Nsp15 [ 13 ] ( Fig. 1 C), and Human Angiotensin-Converting Enzyme 2 (ACE2), the cellular entry receptor for SARS-CoV-2 [ 14 , 15 ] were specifically selected for validation by RT-PCR and IHC. Additionally, placental RNAseq transcript abundance mapped to ENDOU’s PPI network suggests putative interactions of ENDOU ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it remains unclear if vertical transmission—either intrauterine, intrapartum, or immediately postpartum—of SARS-CoV-2 occurs. 13 , 14 , 15 , 16 , 17 Further evidence concluding whether SARS-CoV-2 can infect the placenta, traverse the placental barrier or induce morphologic changes is needed. Reports have suggested that cell entry of SARS-CoV-2 is mediated through the angiotensin-converting enzyme 2 (ACE2) receptor.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 12 Evidence regarding the occurrence of antepartum or peripartum vertical transmission has been conflicting to date. 13 , 14 , 15 , 16 , 17
AJOG MFM at a Glance
Why was this study conducted?
The association between maternal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and placental histopathology is not well known.
…”
Section: Introductionmentioning
confidence: 99%
“…Lamouroux et al 26 and Mahyuddin et al 27 , mention that many microorganisms are able to violate the maternal immune system barrier through the placenta and result in severe fetal consequences. Viruses can exert dynamic fluctuations in the immune environment of the placenta throughout pregnancy and contribute to changes in fetal susceptibility 27 .…”
Section: Resultsmentioning
confidence: 99%